Ammonia in Aquatic Systems - Ruth Francis-Floyd; Craig Watson; Denise Petty; Deborah B. Pouder (EDIS)
Revised! FA-16, a 5-page illustrated fact sheet by Ruth Francis-Floyd, Craig Watson, Denise Petty, and Deborah B. Pouder, informs aquarists, aquaculturists, and hobbyists about this important water quality parameter, its effect on fish health, the nitrogen cycle that eliminates ammonia from water, how to test for ammonia, and how to manage an ammonia problem. Includes references. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, February 2009.